LEARNING ORGANIZATIONS TO BUILD COMMUNITY EMPOWERMENT - Heryanto Susilo; Ach. Rasyad; Zulkarnain Zulkarnain; Hardika Hardika (Universitas Pendidikan Indonesia, 2022)
The education level of rural communities tends to be low, resulting in them needing help to fulfill their needs optimally. The role of youth as agents of change is the village's potential to make the community more independent through learning communities so that welfare goals are achieved. Therefore, a collaboration between the community in Manggugebang village and Universities (PT), especially the PLS department, is expected to provide benefits in the form of creating a creative economy through the utilization of village potential so that the community can enjoy it as an effort to improve the welfare of the community. Describing and analyzing learning organizations is to build community empowerment in Munggugebang, Benjeng District, Gresik Regency. The research method uses a qualitative approach, and data collection techniques are observation, interviews, and documentation. Data analysis techniques are data collection, reduction, display, and levers. Meanwhile, researchers used dependence, dependence, conformability, and transferability to test the validity of the data. This study shows that the implementation of mentoring gives a significant role in the activities of 1) thinking changes and 2) mental empowerment. 3) creative skills.